2006
DOI: 10.1139/f06-057
|View full text |Cite
|
Sign up to set email alerts
|

Depth-specific patterns in benthic–planktonic food web relationships in Lake Superior

Abstract: In an investigation of the spatial characteristics of Laurentian Great Lakes food webs, we examined the trophic relationship between benthic amphipods (Diporeia) and plankton in Lake Superior. We analyzed the carbon and nitrogen stable isotope ratios of Diporeia and plankton at stations in water column depths of 4–300 m. Neither δ15N nor δ13C of plankton from the upper 50 m of the water column varied significantly with station depth. Diporeia isotope ratios exhibited depth-specific patterns reflecting changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 55 publications
7
56
0
Order By: Relevance
“…As in our study, we recommend that depth distribution data for consumers be used to best determine at which depths Wsh are likely to be feeding during particular times of the year. Though depletion of benthic invertebrate 13 C with depth in South Bay is consistent with these other studies where dreissenids are absent (Sierszen et al 2006;Vander Zanden and Rasmussen 1999), it is possible that the enriched 13 C in South Bay nearshore invertebrates and post-invasion lake whiteWsh may be further exaggerated due to increased benthic algal productivity under increased light penetration (Fernandez et al, in press, possibly associated with dreissenid establishment).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As in our study, we recommend that depth distribution data for consumers be used to best determine at which depths Wsh are likely to be feeding during particular times of the year. Though depletion of benthic invertebrate 13 C with depth in South Bay is consistent with these other studies where dreissenids are absent (Sierszen et al 2006;Vander Zanden and Rasmussen 1999), it is possible that the enriched 13 C in South Bay nearshore invertebrates and post-invasion lake whiteWsh may be further exaggerated due to increased benthic algal productivity under increased light penetration (Fernandez et al, in press, possibly associated with dreissenid establishment).…”
Section: Discussionsupporting
confidence: 86%
“…Whereas Diporeia on Lake Superior demonstrated the greatest change in isotopic signatures between 40 and 300 m (Sierszen et al 2006), various South Bay benthos showed changes of similar magnitude and direction but over much shallower (5-50 m) depth ranges. In agreement with of our Wndings, Vander Zanden and Rasmussen (1999) also demonstrated that both 13 C and 15 N varied between habitat types across a range of lakes, decreasing in 13 C and increasing in 15 N from littoral to profundal habitats.…”
Section: Discussionmentioning
confidence: 88%
“…The d 13 C DOC values are consistent with d 13 C values of phytoplankton in the lake (Keough et al 1996(Keough et al , 1998Sierszen et al 2006). The variation in d 13 C DOC in the stratified lake is limited to the freeze-dried samples from September 2007.…”
Section: Discussionsupporting
confidence: 77%
“…The d 15 N POM in Lake Superior has been measured previously (Pang and Nriagu 1977;Keough et al 1996;Ostrom et al 1998;Harvey and Kitchell 2000;Sierszen et al 2006) and it ranges from -2 to 6.9%, similar to the typical d 15 N (from -5.7 to 10.6%) for freshwater seston (Cloern et al 2002). Most of the earlier studies emphasized local food web dynamics (Keough et al 1996;Harvey and Kitchell 2000), had limited sample sizes, or narrow geographic and temporal extent (Pang and Nriagu 1977;Ostrom et al 1998).…”
Section: Stable Isotopes In Nosupporting
confidence: 52%
“…Most of the earlier studies emphasized local food web dynamics (Keough et al 1996;Harvey and Kitchell 2000), had limited sample sizes, or narrow geographic and temporal extent (Pang and Nriagu 1977;Ostrom et al 1998). There is also a limited knowledge of depth-dependent variation in d 15 M POM (Ostrom et al 1998;Sierszen et al 2006) in the lake, which is known to increase with depth in marine systems (e.g., Saino and Hattori 1980;Altabet 1996;Minagawa et al 2001). Our study presents comprehensive temporal, spatial, and depth-dependent measurements of d 15 M POM in Lake Superior and reports the first ever values, to the best of our knowledge, of d 15 M POM during winter along with an evidence of depth-dependent increase in d 15 M POM .…”
Section: Stable Isotopes In Nomentioning
confidence: 99%